2016
DOI: 10.1189/jlb.4vma0716-316r
|View full text |Cite
|
Sign up to set email alerts
|

Rats with a missense mutation in Atm display neuroinflammation and neurodegeneration subsequent to accumulation of cytosolic DNA following unrepaired DNA damage

Abstract: Mutations in the ataxia-telangiectasia (A-T)-mutated () gene give rise to the human genetic disorder A-T, characterized by immunodeficiency, cancer predisposition, and neurodegeneration. Whereas a series of animal models recapitulate much of the A-T phenotype, they fail to present with ataxia or neurodegeneration. We describe here the generation of an missense mutant [amino acid change of leucine (L) to proline (P) at position 2262 (L2262P)] rat by intracytoplasmic injection (ICSI) of mutant sperm into oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 81 publications
2
30
2
Order By: Relevance
“…Long‐term unrepaired DNA damage results in accumulation of DNA in the cytoplasm of cells which activates the cGAS/STING pathway to induce interferon (IFN) production . This has previously been demonstrated in bone marrow‐derived cells from Atm −/− mice and in isolated cells and tissues from rats lacking ATM expression . However, in tissues analysed here IFNβ was barely detected in any Atm −/− Smg1 gt/+ mice (Figure D).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Long‐term unrepaired DNA damage results in accumulation of DNA in the cytoplasm of cells which activates the cGAS/STING pathway to induce interferon (IFN) production . This has previously been demonstrated in bone marrow‐derived cells from Atm −/− mice and in isolated cells and tissues from rats lacking ATM expression . However, in tissues analysed here IFNβ was barely detected in any Atm −/− Smg1 gt/+ mice (Figure D).…”
Section: Discussionsupporting
confidence: 55%
“…Atm knockout (−/−) mice are prone to the development of thymic lymphomas, are radiosensitive and show evidence of oxidative damage to tissues . Furthermore, loss of ATM and the resultant accumulation of unrepaired DNA damage can lead to activation of innate immune pathways and basal inflammation . SMG1 has a well‐characterized role in nonsense‐mediated decay (NMD), the pathway used by cells to detect and degrade mRNA with premature termination codons which may code for truncated proteins .…”
Section: Introductionmentioning
confidence: 99%
“…This process was exacerbated by irradiation. Our work has further shown that this autoinflammatory process occurs in both glia and neurons in the brain and spinal cord of Atm − / − rats and also that there is activation of the NF‐κB signaling pathway and upregulation of IL‐1β . Whether inflammasomes are also activated in response to this build‐up of cytoplasmic DNA is under investigation.…”
Section: Atmmentioning
confidence: 60%
“…For example, loss of ATM has long been known to lead to the accumulation of unrepaired DNA damage but recent studies have shown that this DNA damage can lead to a build‐up of DNA in the cytoplasm of cells leading to inflammation . Our work has shown that this process can occur in neurons in an animal model of the disease ataxia‐telangiectasia and that targeting the induced inflammation can limit disease progression . This review will examine the family members and what is known about their roles in inflammation and consequent disease.…”
Section: Introductionmentioning
confidence: 98%
“…The recently described Atm knockout rat model does not display cerebellar atrophy, however spinal cord atrophy and paralysis were observed (Quek et al, ; Quek et al, ). There was significant loss of motor neurons and activation of microglia in the spinal cord, consistent with a neuroinflammatory phenotype.…”
Section: Introductionmentioning
confidence: 99%